A randomized controlled trial of the different impression methods for the complete denture fabrication: Patient reported outcomes. Issue 8 (August 2015) - Jo, Ayami; Kanazawa, Manabu; Sato, Yusuke; Iwaki, Maiko; Akiba, Norihisa; Minakuchi, Shunsuke
Abstract Objectives To compare the effect of conventional complete dentures (CD) fabricated using two different impression methods on patient-reported outcomes in a randomized controlled trial (RCT). Methods A cross-over RCT was performed with edentulous patients, required maxillomandibular CDs. Mandibular CDs were fabricated using two different methods. The conventional method used a custom tray border moulded with impression compound and a silicone. The simplified used a stock tray and an alginate. Participants were randomly divided into two groups. The C-S group had the conventional method used first, followed by the simplified. The S-C group was in the reverse order. Adjustment was performed four times. A wash out period was set for 1 month. The primary outcome was general patient satisfaction, measured using visual analogue scales, and the secondary outcome was oral health-related quality of life, measured using the Japanese version of the Oral Health Impact Profile for edentulous (OHIP-EDENT-J) questionnaire scores. Results Twenty-four participants completed the trial. With regard to general patient satisfaction, the conventional method was significantly more acceptable than the simplified. No significant differences were observed between the two methods in the OHIP-EDENT-J scores. Conclusions This study showed CDs fabricated with a conventional method were significantly more highly rated for general patient satisfaction than a simplified. Clinical significance CDs, fabricated with the conventional method that included a preliminary impression made using alginate in a stock tray and subsequently a final impression made using silicone in a border moulded custom tray resulted in higher general patient satisfaction. Trial registration UMIN000009875.